How to attract an audience at a conference: Paper, person or place? - Isabel Günther; Melanie Grosse; Stephan Klasen (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2016)
We analyze the drivers of the size of the audience and number of questions asked in parallel sessions at the annual conference of the German Economics Association. We find that the location of the presentation is at least as important for the number of academics attending a talk as the combined effect of the person presenting and the paper presented. Being a presenter in a late morning session on the second day of a conference, close to the place where coffee is served, significantly increases the size of the audience. When it comes to asking questions, location becomes less important, but smaller rooms lead to more questions being asked (by women). Younger researchers as well as very senior researchers attract more questions and comments. There are also interesting gender effects. Women attend research sessions more diligently than men, but seem to ask fewer questions than men. Men are less likely to attend presentations on health, education, welfare, and development economics than women. Our findings suggest that strategic scheduling of sessions could ensure better participation at conferences. Moreover, different behaviors of men and women at conferences might also contribute to the lack of women in senior scientist positions.
Keywords: A11; B54; 330; Economists; Conference; Preferences; Gender Differences